Teachers Readiness Towards the Implementation of HOTS in Teaching Malay Language Essay Writing Skills at Primary Schools: Concept Paper - Bashah, Nor Azzian; Lambri, Alizah (Jurnal Pendidikan Bitara UPSI, 2024)
Higher Order Thinking Skills (HOTS) is one of the elements emphasized by the Malaysian Ministry of Education (KPM) in making the Malaysian Education Development Plan (PPPM) 2013-2025 a success. The integration of KBAT across the curriculum includes all subjects, including Bahasa Melayu, involving skills such as writing. However, there are still challenges faced by teachers, especially in primary schools, in implementing and applying KBAT in teaching essay writing skills in the classroom. One of the obstacles is that teachers do not have sufficient readiness to implement KBAT during teaching. Therefore, this study aims to explore the readiness levels of teachers in implementing KBAT during teaching of Malay language essay writing skills in primary schools. Participants in this study consist of Malay language teachers selected through purposive sampling. This concept paper proposes a qualitative approach using semi-structured interviews, observations, and document analysis. Currently, most studies analyzing teachers’ readiness levels towards KBAT to use quantitative approaches or mixed methods. Hence, this concept paper also aims to diversify the analytical framework by utilizing a purely qualitative approach. The proposed method of analysis is thematic analysis, involving coding and data organization to draw conclusions. Through the development of this concept paper, it is hoped to provide a clear understanding of the readiness levels of Malay language teachers towards KBAT and to address issues in implementing KBAT in teaching writing skills.